10x²+5x=025-100x²=02x²-14=02x²-8=04x²-12=0x²-10x=04x²+20x=02x²+x=03x²-27=04x²+20x=0

10x²+5x=0

25-100x²=0

2x²-14=0

2x²-8=0

4x²-12=0

x²-10x=0

4x²+20x=0

2x²+x=0

3x²-27=0

4x²+20x=0

 

    4X^2 - 12=0; 4X^2 = 12; X^2 = 3 ; X = V 3

     

     

     

     

    25 - 100X^2 = 25*(1 - 4X^2) = 25*(1 - 2X)(1+2X) --> X 1 = +0.5  X2 = - 0.5

     

     

     

    2X^2 - 8 = 0; 2X^2 = 8; X^2 = 4; X1= 2;X2 = -2

     

     

     

     

     

    4X^2 + 20X = 0; 4X(X + 5) = 0; X = - 5

    4X^2 + 20X = 0; 4X(X + 5)=0--> X = - 5

    2X^2 + X = 0; X(X + 1) = 0 --> X = - 1

  • 5X(2X +1) = 0 --> X = - 0.5

     

    3X^2 - 27 = 0; 3(X^2 - 9)=0; 3(X-3)(X+3)=0--> X1 = 3; X2 = - 3

     

     

     

     

    x^2 - 10X = 0 ; X(X - 10) = 0--> X = 10

     

    25X^2 - 14 = 0; 25X^2 = 14 ;X^2 = 0.56 --> X = V 0.56